The Use of E-Modules to Improve Critical Thinking Skills of Physics Education Students - Sri Purwaningsih; Hebat Shidow Falah; Febri Berthalita Pujaningsih (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills are essential in physics education, particularly in understanding abstract concepts like wave functions in quantum mechanics. However, traditional teaching methods often fail to foster these skills effectively. This study explores the use of an interactive e-module titled Quantum Physics: Wave Function to enhance critical thinking skills among students in a physics education program. A quasi-experimental design was employed with an experimental group using the e-module and a control group following conventional methods. Pretest and posttest results showed a significant improvement in critical thinking skills for the experimental group (average increase: 26.30) compared to the control group (average increase: 11.70). Statistical analysis confirmed the e-module's effectiveness (t = 2.95, p = 0.01). The e-module fostered active participation, problem-solving, and independent exploration, demonstrating its potential to improve critical thinking and engagement in complex physics topics. These findings highlight the value of integrating technology into physics education to enhance learning outcomes.